THE EFFECT OF TAX PLANNING AND DEFERRED TAX LIABILITIES ON EARNS MANAGEMENT - Zulfa Rosharlianti; Rahmat Hidayat (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2019)
This researched are intended to analyze the effect of planning tax and deferred tax liabilities on earn management. Manufacturing companies listing on the IDX from 2013 to 2017 are the object of research. This research uses secondary data on annual reports obtained through the sites www.idx.co.id. Purposive sampling is the method used in sampling, with population of 132 entity and the sample in this research are 10 entities the observation period of 5 years, with the result that obtained 50 samples. The method data analysis of this research used multiple regression analysis with the SPSS version 24.The results shows that the tax planning has a negative effect on earn management, neither the deferred tax liabilities does not have effect on earn management. Simultaneously the tax planning and deferred tax liabilities have a positive effect on earn management.